PENGARUH STRATEGI PEMASARAN TERINTEGRASI TERHADAP KEPUTUSAN LAYANAN PRODUK DENGAN PERFORMA PERUSAHAAN SEBAGAI VARIABEL MODERASI - HIDAYAT, HAYATUL (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2025)
Digital transformation has reshaped marketing paradigms; however, its implementation in 3T regions (frontier, outermost, and disadvantaged areas) faces challenges of infrastructure and resource limitations. This study aims to examine an integrated marketing strategy framework based on three core dimensions—consumer observation, internal analysis, and digital marketing—and to assess the moderating role of firm performance on service decision-making. A quantitative survey was conducted with 100 customers of Tab Komputer in Wamena, Papua Highlands, and the data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.The findings reveal that firm performance does not moderate the relationships between marketing strategy or internal analysis and service decisions, as both variables exert a direct and significant influence. Conversely, firm performance negatively moderates the relationship between digital marketing and service decisions, indicating that the effectiveness of digital marketing decreases as corporate reputation and performance improve. This result aligns with the literature on brand equity, signaling theory, and advertising fatigue.Theoretically, this study extends the Resource-Based View and Dynamic Capabilities perspectives by emphasizing the role of internal capabilities and consumer observation in resource-constrained markets, while introducing the concept of restricted social space as an indirect resource influencing service decisions. Practically, the study recommends that SMEs in 3T areas adopt consumer-oriented strategies, strengthen internal analysis, and adjust the intensity of digital marketing according to their performance levels.